A Window of Opportunity: Targeting Cancer Endothelium to Enhance Immunotherapy - Duru, Gizem; van Egmond, Marjolein; Heemskerk, Niels (Frontiers in Immunology, 2020)
Vascular abnormalities in tumors have a major impact on the immune microenvironment in tumors. The consequences of abnormal vasculature include increased hypoxia, acidosis, high intra-tumoral fluid pressure, and angiogenesis. This introduces an immunosuppressive microenvironment that alters immune cell maturation, activation, and trafficking, which supports tumor immune evasion and dissemination of tumor cells. Increasing data suggests that cancer endothelium is a major barrier for traveling leukocytes, ranging from a partial blockade resulting in a selective endothelial barrier, to a complete immune infiltration blockade associated with immune exclusion and immune desert cancer phenotypes. Failed immune cell trafficking as well as immunosuppression within the tumor microenvironment limits the efficacy of immunotherapeutic approaches. As such, targeting proteins with key roles in angiogenesis may potentially reduce immunosuppression and might restore infiltration of anti-tumor immune cells, creating a therapeutic window for successful immunotherapy. In this review, we provide a comprehensive overview of established as well as more controversial endothelial pathways that govern selective immune cell trafficking across cancer endothelium. Additionally, we discuss recent insights and strategies that target tumor vasculature in order to increase infiltration of cytotoxic immune cells during the therapeutic window of vascular normalization hereby improving the efficacy of immunotherapy.